2020
DOI: 10.3390/cancers12123842
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Chemotherapy Related Cognitive Impairment and the Impact of the Alzheimer’s Disease Risk Factor APOE

Abstract: Cancer related cognitive impairment (CRCI) is a serious impairment to maintaining quality of life in cancer survivors. Cancer chemotherapy contributes to this condition through several potential mechanisms, including damage to the blood brain barrier, increases in oxidative stress and inflammation in the brain, and impaired neurogenesis, each of which lead to neuronal dysfunction. A genetic predisposition to CRCI is the E4 allele of the Apolipoprotein E gene (APOE), which is also the strongest genetic risk fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 199 publications
(234 reference statements)
0
21
0
Order By: Relevance
“…However, even these behaviors provide opportunities for demonstrating how specific drugs or treatments may affect behavior in genotype‐specific ways within APOE mouse colonies. For example, we have reported that an anthracycline, doxorubicin, impaired Barnes Maze behavior only in APOE4 mice (Demby et al, 2020; Speidell et al, 2019), supporting the sensitivity of APOE4 individuals to cognitive impairment related to cancer chemotherapy (H. R. Fernandez et al, 2020; Grootendorst et al, 2005).…”
Section: Discussionmentioning
confidence: 85%
“…However, even these behaviors provide opportunities for demonstrating how specific drugs or treatments may affect behavior in genotype‐specific ways within APOE mouse colonies. For example, we have reported that an anthracycline, doxorubicin, impaired Barnes Maze behavior only in APOE4 mice (Demby et al, 2020; Speidell et al, 2019), supporting the sensitivity of APOE4 individuals to cognitive impairment related to cancer chemotherapy (H. R. Fernandez et al, 2020; Grootendorst et al, 2005).…”
Section: Discussionmentioning
confidence: 85%
“…Apolipoprotein E (APOE), a complex glycolipoprotein that facilitates the uptake, transport, and distribution of cholesterol and other lipids, has been studied extensively in relation to cognitive functioning (16). The isoform ε4 has been associated with more pronounced cognitive decline with aging, following insult to the brain, and with a variety of disorders with prominent cognitive dysfunction (e.g., Alzheimer's disease, [16][17]. The isoform ε4's effect on cognitive decline is attributed to reduced neuronal and vascular repair, increased oxidative stress and in ammation, decreased production of neural progenitor cells, impairment of the blood brain barrier, and morphologic differences in brain structure (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…The isoform ε4 has been associated with more pronounced cognitive decline with aging, following insult to the brain, and with a variety of disorders with prominent cognitive dysfunction (e.g., Alzheimer's disease, [16][17]. The isoform ε4's effect on cognitive decline is attributed to reduced neuronal and vascular repair, increased oxidative stress and in ammation, decreased production of neural progenitor cells, impairment of the blood brain barrier, and morphologic differences in brain structure (17)(18)(19). APOE ε4 has been associated with poorer cognitive outcomes in patients with breast cancer and lymphoma (20)(21), testicular cancer (22) and brain tumors (23).…”
Section: Introductionmentioning
confidence: 99%
“…It also plays a crucial role in the maintenance of BBB, as well as in processes of oxidative stress, inflammation, and neuronal health. APOE can produce three alleles, but only the presence of APOE4 is considered as one of the possible risk factors for chemobrain development ( Fernandez et al, 2020 ). Cognitive impairment might occur regardless of used therapy, as it was observed in the cohort study on lymphoma and breast cancer survivors.…”
Section: Central Neurotoxicity: Chemobrainmentioning
confidence: 99%